(untitled) - Chiasson, Robert B. (Dubuque, IA, 1997)
This extensively updated manual is designed for an elementary course in vertebrate biology, and will also complement a variety of courses in general biology, zoology, or basic anatomy.
Keywords: Swine,Swine; Fetuses,Anatomy,Laboratory manuals,Fetuses,Dissection,Laboratory manuals